PP.39 Teenage Pregnancy – A Decade Since the UK Department of Health Teenage Pregnancy Strategy Plan: A Review in a University Teaching Hospital in London, UK. (26th April 2013) - Burrell, C; Wright, S; O'Connor, H; Shaw, S; Cornell, A
Abstract : Background: (1) In 1999, the UK DOH Teenage Pregnancy Strategy Plan pledged to reduce the pregnancy rate by 50% in < 18 yrs old by 2010. (2) In 2009, the UK teenage pregnancy rate was 38.3 per 1, 000 compared to 54.3 per 1, 000 in Barking & Dagenham (high-risk area served by the hospital) Aim: This retrospective cohort study reviewed all viable teenage pregnancies from Jan 1, 2010–Dec 31, 2010. Method: Data were obtained from the Labour Ward, Birth Notification and Operating Theatre Registries. Results: There were 257 teenagers with 260 viable babies > 28 weeks gestation. This included primigravida (230/257) = 89.49% and multiparous (27/257) = 10.51%. The ages ranges from 14–19 yrs (mean = 18.29 yrs). Ten (10/257) 3.89% were < 16 yrs old. There were Instrumental deliveries (29/257) = 11.28%, Caesarean section (36/257) = 14.01%, and Vaginal deliveries (192/257) = 74.71%. The mean fetal birth weights were – Instrumental 3.389 kg +/- SD 0.468 kg, Caesarean 3.106 kg +/- SD 0.752 kg; and Vaginal Delivery 3.117 kg +/- SD 0.501 kg. Maternal Morbidity: Third degree tear (n = 3), Pre-eclampsia (n = 12) & PPH > 1 litre (n = 4) Fetal Morbidity: SCBU admission (n = 7), Stillbirth (n = 3) & Shoulder dystocia (n = 2) Discussion: During 1999–2009 the teenage pregnancy rate fell by only 13.3% in spite of the DOH Teenage Pregnancy Strategy Plan. In this cohort the caesarean rate was lower 14.01% vs 24%, the vaginal delivery higher 74.71% vs 65% but the instrumental was similar 11.28% vs 10% compared to the UK average (Caesarean Section Sentinel Audit). There was a dedicated Teenage Pregnancy Midwifery Team providing continuity of care There were 10.51% (27/257) multiparous teenagers thus contraceptive advice remains crucial, as UK has the highest teenage pregnancy rate in Europe